Metabolism and growth performance of pacu (Piaractus mesopotamicus) juveniles submitted to different feeding frequencies (Research, Society and Development, 2021)
The aim of this study was to evaluate the effects of different feeding frequencies on productive performance, hepatocytes integrity, frequency of muscle fibers distribution, enzymatic activity, and proximate composition of pacu juveniles (Piaractus mesopotamicus). One hundred and sixty fish were distributed in 20 tanks arranged in a recirculation system. The proposed managements of feed offer were the partition of the daily amounts into one, two, three or four times during 60 days. Feed consumption were higher in fish fed four times a day, whilst the hepatosomatic index was higher in fish fed once, but similar to fish that received food two or four times a day. As for plasmatic glucose levels, fish fed twice a day displayed an increase in this parameter. The livers of fish fed two or four times a day presented larger hepatocytes and cellular nuclei. Regarding the proximate composition of carcasses, fish that received one daily feeding presented higher ether extract. It was concluded that feeding frequency is a factor that promotes changes in P. mesopotamicus nutritional metabolism, thus the offer of feed four times a day could be recommended for this species in this life stage.